2021
DOI: 10.1021/acs.est.1c03798
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Halogenated Organic Compounds in Pelagic Sharks and Sea Turtles Using a Nontargeted Approach

Abstract: Halogenated organic compounds (HOCs) in marine species collected from the Atlantic Ocean [3 shortfin mako (Isurus oxyrinchus) and 1 porbeagle (Lamna nasus)], and 12 sea turtles collected from the Pacific Ocean [3 loggerhead (Caretta caretta), 3 green (Chelonia mydas), 3 olive ridley (Lepidochelys olivacea), and 3 hawksbill (Eretmochelys imbricata)] were analyzed with a nontargeted analytical method using two-dimensional gas chromatography coupled to high-resolution time-of-flight mass spectrometry. Sharks and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 81 publications
(158 reference statements)
0
9
0
Order By: Relevance
“…The mass feature ratio extracted through mixed-SPE is 1.10–1.72 times higher than that of PPL-SPE across the five treatment plants. While variations in published studies (e.g., formula assignment strategies, mass range, element composition, pretreatment, and analytical conditions) must be considered, the amount of Cl-/Br-containing DOM in leachate matrices appears considerably higher compared to sewage and biota samples, thereby heightening the risk. Under this limited benchmark, the lowest is up to 2.10 times, while considering all of the leachates and concentrates, the highest is up to 5.03 times.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The mass feature ratio extracted through mixed-SPE is 1.10–1.72 times higher than that of PPL-SPE across the five treatment plants. While variations in published studies (e.g., formula assignment strategies, mass range, element composition, pretreatment, and analytical conditions) must be considered, the amount of Cl-/Br-containing DOM in leachate matrices appears considerably higher compared to sewage and biota samples, thereby heightening the risk. Under this limited benchmark, the lowest is up to 2.10 times, while considering all of the leachates and concentrates, the highest is up to 5.03 times.…”
Section: Resultsmentioning
confidence: 99%
“…Unknown Cl-/Br-containing DOM in complex waste-derived water samples can be promisingly interpreted via halogenated isotopic ratio and mass defect filter strategies, not limited to biota and natural samples. 1,17,21,22 Meanwhile, mainstream sample pretreatment for DOM analysis via HRMS should be optimized accordingly to decipher more Cl-and Br-containing DOM in the leachate matrices. Solid-phase extraction (SPE) has become a wellestablished and widespread DOM isolation method with high organic matter recovery and less solvent consumption, wherein sorbents, such as XAD, silica-C18, modified styrene divinylbenzene polymer (PPL), and hydrophilic−lipophilic polymer (HLB), are most commonly used.…”
Section: Introductionmentioning
confidence: 99%
“…Earlier work clearly demonstrated that a naturally produced compound such as DAME is persistent in the environment (10) and able to bioaccumulate in organisms (7)(8)(9). DAME and DA exhibit antimicrobial properties that may serve as the wood fungi's chemical defense against organisms that compete for the same substrate (19).Therefore, it is possible that they exert toxic effects similar to those other biocides.…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, the sources of such naturally occurring substances are often difficult to define. Polyhalogenated carbazoles are a group of widely spread contaminants found in aquatic species . The compounds are known to have dual origins, produced naturally by marine cyanobacteria and also synthesized as intermediates to meet the industry needs since the 1900s …”
Section: Basic Principles On Recognition Of Environmental Orgainc Pol...mentioning
confidence: 99%